Do strategic leadership and self efficacy among school leaders make a difference? - Mohd Ali, Hairuddin; Ali, Aniyath (Published by Canadian Center of Science and Education, 2015)
Leadership Characteristics of Maldivian school leaders and their Leadership Self-efficacy. The study employed a survey approach and the data were collected using an adapted seven point Likert scale survey questionnaire. Data were collected from 23 schools in the capital city Male’, Republic of Maldives. A total of 200 school leaders (45 males and 155 females) participated in the study. The data were analyzed using descriptive statistics, Pearson product-moment correlation and Structural Equation Modeling. The findings of the study revealed that the school leaders in Male’ possessed all nine characteristics of strategic leadership. It also indicated that school leaders’ in Male’ have quite a bit of control in their roles as school leaders, revealing a high perception level of self-efficacy. Moreover, the results of the correlation analysis and examination of path analysis indicated that there was statistically significant and positive relationship between Strategic Leadership Characteristics of Maldivian school leaders and their Leadership Self-efficacy. The present study provides a starting-point for further exploring the strategic leadership qualities and self-efficacy of school leaders which are vital to bring a positive reform in schools. This study highlights that executing strategic leadership is essential to deal with both the need for sustainable change. It further indicates that both self-efficacy and strategic leadership are important to school leaders’ as they affect performance of the leaders through different mechanisms. Keywords: strategic leadership, leadership self-efficacy, Maldives, school leaders, structural equation modeling